BALI PUPPET IN CONTEMPORARY PAINTING ART - Yoga, I Wayan Swantara; Mudana, I Wayan; Kondra, I Wayan (Program Studi Seni Murni ISI Bali, 2025)
The independent campus learning program is a policy of the Minister of Education and Culture, which aims to encourage students to master various knowledge that is useful for entering the world of work. This independent project study report highlights the concept of Balinese Shadow Puppetry in Contemporary Painting. Departing from the rare Shadow Puppetry which has become one of the inspirational ideas for creating art. The selection related to Shadow Puppet visuals in the creation of this work of painting presents the story of wayang as expressed through 6 (six) works of Painting. The problem faced is the concept, method and embodiment of Balinese Shadow Puppetry in Contemporary Painting. The aims and benefits are to provide a reflection on the creation of Balinese Shadow Puppets in Contemporary Painting. To answer the problems above, the creation method is a solution by applying exploration, improvisation, forming. Soedarsono (2001: 207), in realizing his work, the author used his own techniques or (experiments) combined with Shadow Puppet visuals and combined them with the characteristic ornaments of Sanggar Wasundari. Wet technique and application of color from Shadow Puppet and Kamasan Puppet. It is hoped that it can produce quality work and become the identity of the creator. In the end, it can be concluded that Balinese Shadow Puppets can inspire writers in creating valuable and meaningful works. With the creation of this work, it is hoped that it will be able to convey the message in this work of painting.